A Comparative Study of Economic Efficiency of Sorghum in Monoculture and Intercropping Patterns in Ende District, Indonesia - Willybrordus Lanamana; Reyna Virginia Nona (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2025)
Sorghum is one of the rice substitution commodities, and a source of carbohydrates, protein, vitamins and minerals, however, the percentage of its productivity witnessed a decrease. This research aims to analyze the economic efficiency level of sorghum cultivation through the development of monoculture and intercropping agricultural models. Additionally, the research is aimed at discovering the fundamental factors that influence the efficiency level. This research was conducted in Nggela village, starting from September to November 2023. The population was 170 participants, consisting of 95 people applying monoculture farming and 75 people for the intercropping farming model. The census method was used in this research. The researchers adopted the Cobb-Douglass Stochastic Frontier Analysis (SFA) approach for data analysis. The results of the study showed that the average technical, allocative and economic efficiency of monoculture sorghum farmers was lower than that of intercropping sorghum farmers; this caused farmers to be more interested in intercropping technology than monoculture. Advantages of intercropping; reducing plant pests, increasing soil fertility, and increasing farm income. Factors that affect technical, allocative and economic efficiency are; age, length of farming, farmer membership dummy, cropping model dummy, and land ownership status dummy and the one that did not have a significant effect was the credit access dummy, This has an impact on the slow development of sorghum farming businesses. It is recommended that farmers adopt intercropping practices and optimize their use of inputs for greater efficiency.